Quality of life in patients with progressive supranuclear palsy: a review of literature and implications for practice - Markiewicz, Michał; Madetko-Alster, Natalia; Alster, Piotr (Frontiers in Neurology, 2024)
Progressive supranuclear palsy (PSP) is an atypical form of parkinsonism characterized by tauopathy, manifesting as oculomotor dysfunction, postural instability, akinesia, and cognitive/language impairments. The diagnosis and examination of PSP can be challenging, primarily due to the unclear and underexplored pathomechanisms involved, alongside absence of effective treatments. Clinical variants of PSP is the second most common form of neurodegenerative parkinsonism after Parkinson’s disease (PD). It is defined by a symmetrical akinetic-rigid syndrome (atypical parkinsonism) and vertical supranuclear gaze palsy. In contrast to PD, PSP often presents with gait instability, backward falls, and cognitive and behavioral changes at early disease stages. The classification of PSP has evolved since Richardson, Steele, and Olszewski’s initial reporting of the condition in 1963, which included a cohort of nine patients. Over the years, the definition of this disorder has evolved to encapsulate a group of patients with distinct clinical variants, notably the classical Richardson syndrome (RS) and several atypical phenotypes, each with significant implications for disease progression and quality of life (QoL). The 2017 Movement Disorder Society Diagnostic Criteria by Hoglinger et al., improved the sensitivity for detecting early and variant PSP presentations and provided more specific differential diagnoses for conditions such as PD and other forms of atypical parkinsonian syndromes. Owing to the growing interest in the disease’s progression, evaluating the QoL for patients with PSP has become crucial. This review emphasizes the significance of QoL evaluation and its feasibility for practical implications, serving as an initial foundation for future research focused on the well-being of individuals affected by PSP. Progressive supranuclear palsy (PSP) is an atypical form of parkinsonism characterized by tauopathy, manifesting as oculomotor dysfunction, postural instability, akinesia, and cognitive/language impairments. Diagnosing PSP is challenging owing to the lack of tools for differential examination. Additionally, the pathomechanism of this disease is not sufficiently understood, and no treatment is currently available. Owing to the growing interest in the disease’s progression, evaluating the quality of life (QoL) for patients with PSP has become crucial. This review emphasizes the significance of QoL evaluation and its feasibility for practical implications, serving as an initial foundation for future research focused on the well-being of individuals affected by PSP.